The Effect of Bay Leaf (Syzygium polyanthum) Decoction on Lowering Blood Pressure in Hypertensive Patients - Syaripudin, Ahmad (Journal of Health and Nutrition Research, 2025)
Hypertension is a chronic disease and a leading cause of global mortality, prompting interest in non-pharmacological therapies. This study aimed to investigate the effect of bay leaf (Syzygium polyanthum) decoction on blood pressure changes in patients with hypertension. This pre-experimental study employed a one-group pre-test-post-test design with 30 hypertensive patients at the Watubelah Public Health Center in Cirebon Regency. The intervention consisted of a decoction of 10 bay leaves boiled in 400 mL of water until 200 mL remained, which was consumed twice daily for seven days. Data were analyzed using the Wilcoxon test. The results showed a significant decrease in the mean systolic blood pressure from 153.6 mmHg to 138.4 mmHg and diastolic blood pressure from 93.8 mmHg to 84.1 mmHg (p = 0.001). This study concludes that bay leaf decoction is associated with a significant reduction in blood pressure in hypertensive patients, suggesting its potential as a complementary therapy in nursing practice.